2021
DOI: 10.33448/rsd-v10i2.12305
|View full text |Cite
|
Sign up to set email alerts
|

Photoprotective activity of geopropolis produced by Melipona subnitida (Apidae, Meliponinae) in the semiarid of the Brazilian Northeast

Abstract: Although geopropolis has been the subject of many chemical and pharmacological studies, there are few studies investigating the photoprotective activity of formulations containing propolis. Thus, we investigated in vivo the photoprotective efficacy of the cream containing geopropolis extract by macroscopic and histological evaluation of the skin of Wistar rats subjected to ultraviolet radiation (UVB). We also evaluated the chemical composition of hydroethanolic extract using the HPLC-DADESI-MS/MS technique, as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 29 publications
1
1
0
1
Order By: Relevance
“…In this assay, the cytotoxic potential of EEGP against HaCaT cells at 24 h was evaluated, showing a reduction in cell viability at all three tested concentrations, with indices of 67.4 % at MICx4. Correlating with assays conducted by Batista et al, [40] the percentage of HaCaT keratinocyte viability at the highest tested concentration was above 60 %. In the experiments of Bomfim de Barros et al, [23] tests using α-Pinene against HaCaT cells, after 48h of treatment, demonstrated viability above 50 % at MIC, being cytotoxic only at MICx4.…”
Section: Discussionsupporting
confidence: 77%
“…In this assay, the cytotoxic potential of EEGP against HaCaT cells at 24 h was evaluated, showing a reduction in cell viability at all three tested concentrations, with indices of 67.4 % at MICx4. Correlating with assays conducted by Batista et al, [40] the percentage of HaCaT keratinocyte viability at the highest tested concentration was above 60 %. In the experiments of Bomfim de Barros et al, [23] tests using α-Pinene against HaCaT cells, after 48h of treatment, demonstrated viability above 50 % at MIC, being cytotoxic only at MICx4.…”
Section: Discussionsupporting
confidence: 77%
“…The sunburn, skin inflammation and skin cancer may appear as a result of regular exposure to UV radiation. These UV rays can promote photochemical reactions that induce the generation of free radicals such as O2 -, HOO -, and OH· (Batista et al 2021). Some studies are in quest for natural sunscreen products to reverse and block these UV radiations.…”
Section: Phenolic Compoundsmentioning
confidence: 99%
“…O autor não Brazilian Journal of Health Review, Curitiba, v. 6, n. 5, p. 25310-25322, sep/oct., 2023 considerou este aumento como significativo. Por outro lado, no artigo publicado porBatista et al, (2021) observou-se um aumento no (FPS) de uma base creme após a incorporação do extrato hidroalcóolico de própolis, elevando o (FPS) in vitro do creme de 8,32 para 20,13.…”
unclassified